Identification and comparison of France to other countries of the teaching of research to nursing students: Results of an international survey of nursing educator. (February 2021) - Devos, Flora; Jilet, Léa; Bouazza, Naïm; Foissac, Frantz; Tréluyer, Jean-Marc; Chappuy, Hélène; Ancel, Pierre-Yves
Abstract: Purpose: Registered nurses must have a level of scientific literacy to be able to interpret research data and access Scientific's knowledge. Several studies have been conducted to explore barriers and levers to the dissemination of nurse's knowledge; however, the scientific literacy that nursing students acquire has not been studied. Objective: The aim was to examine and compare the way that research is taught to undergraduate nursing students in France and other countries. Design: Cross-sectional, Internet survey. Settings: Universities providing undergraduate nursing programs around the world. Participants: Nurses educators. Methods: Schools of nursing and universities were contacted by mail, through social networks and with the help of national or international nursing organizations. Respondents provided demographic data on schools and faculties of nursing, the teaching of scientific databases, Reading Critical Analysis and the teaching of scientific English. Information on the transmission of articles and access to scientific knowledge by students through the institution were also requested. Findings: A total of 245 nursing schools/universities participated. Most respondents were educational research referees (52.2%), worked in a public institution (85.7%) and were in the nursing program leading to a bachelor's degree (74.3%). Databases were taught at 56.8%, Critical Reading of Articles at 70.1%, scientific English at 60.6% of nursing schools or universities. Articles were provided to students at 89.6% of institution and students had access to data through the institution in 66.1% of nursing schools or universities. Several significant differences were found between French schools of nursing and nursing schools/universities in other countries. Conclusions: Our results show that most schools or universities of nursing teach the three majors' components to promote, provide articles to students and give access to scientific knowledge. However, there is wide heterogeneity between countries. There is a need to standardize research education for nursing students worldwide to promote the development of scientific literacy skills. Highlights: The teaching of research in undergraduate nursing programs is request to provide a level of scientific literacy to registered nurses. Research is taught in almost all curricula but the diversity in the composition of teaching may not lead to the same skills. Wide variations were found in the teaching of research between nursing programs in France and other countries. Standardization of the content of research education in nursing universities could be beneficial to nursing students, public health and patients.